ANALISA MANAGEMENT BANDWIDTH MENGGUNAKAN QUEUE TREE SEBAGAI TRAFFIC CONTROL DENGAN METODE PFIFO - Ahmad Syahlan Danu Terto; Eka Purwa Laksana (MAESTRO, 2019)
In this research conducted the research of bandwidth Management which is a technique of setting the amount of bandwidth in uploading and downloading data. Bandwidth Management is done using the queue tree algorithm on the OS Router. In this research method used is the method Pfifo, where the method is applied to the Router OS so that it can be done a comparison to the parameter-Paramer Quality of Service (QoS) before and after applied to the Router OS. The values of the Quality of Service (QoS) parameters are obtained by uploading a data to a website and then downloading the data. In this research, traffic control separates upload and download traffic, while applying packet queues through the OS Router. Results obtained in the form of Internet traffic changes that have exceeded the size of 22MB are moved on heavy traffic.